Study Optoelectronic and Geometric Properties of New compounds Based on Carbazole-thiophene Bridged for Solar Cells - Jabha Mohamed; El Alaoui Abdelah (Orbital: The Electronic Journal of Chemistry, 2018)
Theoretical studies have been carried out to predict the structure, electronic, optical and photovoltaic properties of systems based on carbazole - thiophene bridged and X groups (X1: Benzo-[c]-thiophene, X2: Quinolinn-8-ylamine, X3: Benzyl-amine) with or without the strongly attracting chromophore -CHCO2HCN. The optoelectronic and photovoltaic properties improve when some donor and acceptor blocs alternate on the oligomer skeleton since slight band gap are noticed especially for X2 and X3 molecules with chromophore (average value 2.59eV). Indeed, some higher values of λmax (wave-length absorbed) are obtained and the HOMO and LUMO orbitals are correctly located than their homologs semi-conductors like the bis adduct of phenyl-C61-butyric acid methyl ester (Bis-PC61BM).DOI: http://dx.doi.org/10.17807/orbital.v10i7.1322